Effectiveness of a treatment guideline for schizophrenia in adolescents: Lessons from a middle-income country. (February 2018) - Ulloa, Rosa-Elena; Arce, Sofía; Victoria, Gamaliel; Sarmiento, Emmanuel; Jiménez, Israel; Arroyo, Eduardo; Díaz Calvo, Ana-Teresa; Del Valle, Miriam; Santos, Gabriela; Rosetti, Marcos; Apiquian, Rogelio
Introduction: Treatment guidelines for schizophrenia represent a standard way to manage patients, especially in countries with limited staff resources. However, they have not been compared on their efficacy with treatment as usual, despite adult studies suggesting they can be more effective. Methods: Inpatient and outpatient adolescents with schizophrenia were randomly allocated to be either treated according to a guideline-based treatment ( n = 43) or treatment as usual ( n = 44). The effects on symptoms, psychosocial functioning and cognition were compared in a 6-month follow-up. Results: There were no differences between groups in the pharmacological treatment, reduction in symptom severity or cognition. The guideline-based treatment group showed a better functioning at months 3 and 6. Conclusion: The guideline-based treatment had a greater effect than the treatment as usual in the psychosocial functioning of adolescent patients (www.clinicaltrials.gov ; II3/02/0811).